Brain Activation during Memory Encoding in Type 2 Diabetes Mellitus: A Discordant Twin Pair Study - Amanda G. Wood; Jian Chen; Christopher Moran; Thanh Phan; Richard Beare; Kimberley Cooper; Stacey Litras; Velandai Srikanth (Journal of Diabetes Research)
Type 2 diabetes mellitus increases the risk of dementia and neuronal dysfunction may occur years before perceptible cognitive decline. We aimed to study the impact of type 2 diabetes on brain activation during memory encoding in middle-aged people, controlling for age, sex, genes, and early-shared environment. Twenty-two twin pairs discordant for type 2 diabetes mellitus (mean age 60.9 years) without neurological disease were recruited from the Australian Twin Registry (ATR) and underwent functional magnetic resonance imaging (fMRI) during a memory encoding task, cognitive tests, and structural MRI. Type 2 diabetes was associated with significantly reduced activation in left hemisphere temporoparietal regions including angular gyrus, supramarginal gyrus, and middle temporal gyrus and significantly increased activation in bilateral posteriorly distributed regions. These findings were present in the absence of within-pair differences in standard cognitive test scores, brain volumes, or vascular lesion load. Differences in activation were more pronounced among monozygotic (MZ) pairs, with MZ individuals with diabetes also displaying greater frontal activation. These results provide evidence for preclinical memory-related neuronal dysfunction in type 2 diabetes. They support the search for modifiable later-life environmental factors or epigenetic mechanisms linking type 2 diabetes and cognitive decline.